Congenital vitiligo. - Patil, S.; Mitra, D. (European Journal of Pediatric Dermatology, 2024)
Vitiligo is a frequent acquired pigmentation disease which, although rarely, can be present at birth, as in the current case, observed by us at the age of 8 with stable vitiligo, white forelock and poliosis of the eyelashes. The case was presented to discuss the difficulties encountered in excluding various syndromic associations and management strategies.